The intended purpose and regional patterns of use of antibiotics for managing Clostridioides (Clostridium) difficile infections: An analysis of the National Database of Health Insurance Claims and Specific Health Checkups data of Japan. Issue 2 (February 2022) - Inose, Ryo; Muraki, Yuichi; Kamimoto, Yoko; Kusama, Yoshiki; Koizumi, Ryuji; Yamasaki, Daisuke; Ishikane, Masahiro; Tanabe, Masaki; Ohmagari, Norio
Abstract: Introduction: We previously showed the trend of antimicrobial use (AMU) for Clostridioides ( Clostridium ) difficile infection (CDI) using sales data. However, the details of the prescribing medical institutions and regional characteristics are unknown. Therefore, the purpose of this study was to clarify the details of the medical institutions where antibiotics for CDI were prescribed, and evaluate the AMU for CDI and the regional characteristics. Methods: Antibiotics for CDI, including oral vancomycin (VCM), oral metronidazole (MNZ), and intravenous (IV) MNZ, were collected from the National Database of Health Insurance Claims and Specific Health Checkups (NDB) between 2013 and 2016. The PID (patients/1000 inhabitants/day) was used as an evaluation index for AMU. The PID was calculated using the claim types: inpatient, outpatient, dental, and pharmacy. The PID of each prefecture was calculated for inpatient claims in 2016. Results: The AMU of oral VCM and IV MNZ were observed mainly in the inpatient claims. For oral MNZ, the total AMU in the outpatient and pharmacy claims accounted for approximately 80% per year throughout the study period. For inpatient claims of each prefecture in 2016, the PID of the antibiotics used for CDIs was approximately 3.5 times the difference between the highest and lowest prefectures. Conclusions: The AMU for CDI that takes into account the purpose of use was clarified by using the information of the prescribed medical institutions that were included in the NDB. Oral MNZ was used frequently in outpatients, and attention should be paid to the acquisition of resistance.